Raman Spectroscopy of six explanted acrylic hydrophobic foldable intraocular lenses with glistening - Harsha Bhattacharjee; Kasturi Bhattacharjee; Dipankar Das; Henal Javeri; Suklengmung Buragohain (Indian Journal of Ophthalmology, 2022)
Purpose: To study and interpret Raman spectra of six explanted acrylic hydrophobic foldable intraocular lenses (HFIOLs) with grade six microvacuoles and to understand the possible mechanism for microvacuole formation. Methods: Clinical data, slit-lamp photographs, and optical microphotographs of the explanted analytes were obtained. RS of the analytes were registered using a confocal Raman microscope (Lab RAM HR Evolution, Horiba Jobin Yvon) and Horiba Lab Space 6 Spectroscopy Suite software. Data were interpreted by identifying the functional group and fingerprint region of the spectra about the available literature. Results: IOLs were explanted for visual impairment after an average interval of 11.2 years following implantation. Each of the HFIOLs exhibited distinctive and identical Raman bands at the frequency range of 200–1,800, 2,600–3,000, and 3,200–3,700 cm-1 which were identified with those reported in the literature. The unique bands and peaks of the spectra were specific to the functional groups, its ring and other stretching variations, hydroxyl group, and water molecule. A spike at 1,640 cm-1 revealed the presence of monomer and indicated material bioincompatibility of the samples. Conclusion: Raman spectroscopy (RS) was found specific and an effective tool to detect the material change in the HFIOL and constituents of polymer biomaterial about microvacuole formation and also suggested modification and development of a more biocompatible and non-biodegradable polymer blend where RS could be a monitoring tool.